Metabolic characteristics of recombinant Chinese hamster ovary cells expressing glutamine synthetase in presence and absence of glutamine - Zhang, Fang (Springer Netherlands, 2006)
To elucidate the metabolic characteristics of recombinant CHO cells expressing glutamine synthetase (GS) in the medium with or without glutamine, the concentrations of extra- and intracellular metabolites and the activities of key metabolic enzymes involved in glutamine metabolism pathway were determined. In the absence of glutamine, glutamate was utilized for glutamine synthesis, while the production of ammonia was greatly decreased. In addition, the expression of recombinant protein was increased by 18%. Interestingly, the intracellular glutamine maintained almost constant, independent of the presence of glutamine or not. Activities of glutamate-oxaloacetate aminotransferase (GOT), glutamate-pyruvate aminotransferase (GPT), and glutamate dehydrogenase (GDH) increased in the absence of glutamine. On the other hand, intracellular isocitrate and the activities of its downstream isocitrate dehydrogenase in the TCA cycle increased also. In combination with these two factors, a 8-fold increase in the intracellular α-ketoglutarate was observed in the culture of CHO-GS cells in the medium without glutamine.